IMPACT EVALUATION OF THE 'BOLSA DA MÃE' SOCIAL ASSISTANCE PROGRAM ON IMPROVING CHILDREN'S ACCESS TO EDUCATION AND HEALTH IN DILI, TIMOR LESTE - Simeão Fatima Martins, Patricia Baliana da Costa, Carolina da Cruz Jaimito Soares, Domingos Loe Soar (FKIP UMN ALWASHLIYAH, 2026)
Conditional Cash Transfer (CCT) programs have become a globally popular policy instrument for breaking the intergenerational cycle of poverty. In Timor-Leste, the 'Bolsa da Mãe' (Mother's Allowance) program was implemented with a similar objective, targeting the most vulnerable families within the nation's socio-economic structure. This study aims to quantitatively evaluate the impact of the Bolsa da Mãe program on improving access to education and health for children from beneficiary families in the urban area of Dili, a context with unique poverty dynamics. Using a quantitative approach with a quasi-experimental (non-equivalent control group) design, this research compares 400 households (200 beneficiaries and 200 non-beneficiaries) matched on key socio-economic characteristics to minimize selection bias. Data was collected through in-depth structured questionnaire surveys and triangulated with secondary data from school records and health center medical records for validation. Inferential data analysis was conducted using an independent samples t-test to compare the mean achievements between the two groups. The results show that the Bolsa da Mãe program has a statistically and practically significant positive impact. The average school attendance rate for children from beneficiary families reached 94.5%, a substantial difference of 13.3 percentage points compared to 81.2% in the non-beneficiary group (p < 0.05). In terms of health, 91% of children from beneficiary families had received complete basic immunizations, far exceeding the 75% figure in the non-beneficiary group (p < 0.05). These findings indicate that Bolsa da Mãe functions not only as a social safety net that mitigates economic shocks but also as an effective human capital investment tool at the household level. The primary recommendations are for the government to strengthen compliance monitoring mechanisms digitally to enhance efficiency and to consider integrating the program with complementary services, such as nutrition education and sanitation programs, to maximize long-term impacts on human development.